2017
DOI: 10.1111/ijd.13564
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T‐cell cytokines in patients with nonsegmental vitiligo

Abstract: In the etiopathogenesis of vitiligo, the role of suppressor cytokines, such as transforming growth factor-β (TGF-β) and interleukin-10 (IL-10), associated with regulatory T-cells (Treg) is not completely known. In this study, the role of Treg-cell functions in the skin of patients with nonsegmental vitiligo was investigated. Lesional and nonlesional skin samples from 30 adult volunteers ranging in age from 18 to 36 years with nonsegmental vitiligo were compared with normal skin area excision specimens of 30 be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Previously, significantly reduced IL-10 and TGF-β mRNA and protein levels were reported in serum/skin of GV patients. [16,32,[39][40][41][42][43][44] Moreover, the ratio of pro-inflammatory cytokine to anti-inflammatory cytokine was found to be altered in the in vitro suppression assay. In particular, significantly increased ratio of IFN-γ:IL-10 and IFN-γ:TGF-β was observed in Treg:CD8 + T cells and Treg:CD4 + T cells' co-culture systems of GV patients ( Figure S7a-d), suggesting the crucial role of IL-10 and TGF-β deficiency in compromised suppressive capacity of Treg cells in GV ( Figure S13).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, significantly reduced IL-10 and TGF-β mRNA and protein levels were reported in serum/skin of GV patients. [16,32,[39][40][41][42][43][44] Moreover, the ratio of pro-inflammatory cytokine to anti-inflammatory cytokine was found to be altered in the in vitro suppression assay. In particular, significantly increased ratio of IFN-γ:IL-10 and IFN-γ:TGF-β was observed in Treg:CD8 + T cells and Treg:CD4 + T cells' co-culture systems of GV patients ( Figure S7a-d), suggesting the crucial role of IL-10 and TGF-β deficiency in compromised suppressive capacity of Treg cells in GV ( Figure S13).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Zhang et al () have reported reduced serum levels of sCTLA4, IL10, and TGFB in vitiligo patients. The role of IL‐10 in the pathogenesis of vitiligo has been evidenced by several studies demonstrating the reduced levels of IL‐10 in serum (Ala, Pasha, Rao, Komaravalli, & Jahan, ; Tembhre et al, ), in lesional skin (Kidir, Karabulut, Ercin, & Atasoy, ), and in Tregs (Zhang et al, ) of vitiligo patients as compared to controls. The present study also found decreased IL10 transcript in Tregs and decreased IL‐10 protein level in plasma of GV patients as compared to controls (Figure a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between studies about counts of Tregs might be attributed to (1) each sampling reflects merely a cross‐section of a developing disease progression, thus the panorama of changing Treg counts can't be obtained; (2) many other activated CD4 + cells also express FoxP3 and FoxP3 antibodies employed in the experiment can also bind to them 204 ; (3) racial and age factors 194 . Several studies illustrated the notably decreased levels of TGF‐β 195,201,205 and IL‐10 205,206 in the serum of vitiligo patients in contrast to controls. FoxP3 expression in serum and lesional skin, 201 FoxP3 mRNA expression in lesional and perilesional skin declined in vitiligo patients 207 .…”
Section: Adaptive Immune Activationmentioning
confidence: 99%